Design Process for a Birthing Bed, Based on User Hierarchy: Promoting Improvement in User Satisfaction - Fabiola Cortés-chávez; Alberto Rossa Sierra; Elvia Luz González-muñoz (My University, 2021)
The medical device design process has a responsibility to define the characteristics of the object to ensure its correct interaction with users. This study presents a proposal to improve medical device design processes in order to increase user acceptance by considering two key factors: the user hierarchy and the relationship with the patient’s health status. The goal of this study is to address this research gap and to increase design factors with practical suggestions for the design of new medical devices. The results obtained here will help medical device designers make more informed decisions about the functions and features required in the final product during the development stage. In addition, we aim to help researchers with design process didactics that demonstrate the importance of the correct execution of the process and how the factors considered can have an impact on the final product. An experiment was conducted with 40 design engineering students who designed birthing beds via two design processes: the traditional product design process and the new design process based on hierarchies (proposed in this study). The results showed a significant increase in the user acceptance of the new birthing bed developed with the hierarchical-based design process.
Keywords: Design; Birthing bed; Sser-centered design; Medical device design; User hierarchies; Design process; design education; Hierarchies